2014
DOI: 10.1371/journal.pone.0115742
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Based Financial Asset Pricing

Abstract: We investigate entropy as a financial risk measure. Entropy explains the equity premium of securities and portfolios in a simpler way and, at the same time, with higher explanatory power than the beta parameter of the capital asset pricing model. For asset pricing we define the continuous entropy as an alternative measure of risk. Our results show that entropy decreases in the function of the number of securities involved in a portfolio in a similar way to the standard deviation, and that efficient portfolios … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 19 publications
5
47
0
1
Order By: Relevance
“…This finding is consistent with results of Dionisio et al ( , 2007 and Ormos and Zibriczky (2014) who showed the ability of entropy to measure risk in portfolio management.…”
Section: H X Tunindexsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with results of Dionisio et al ( , 2007 and Ormos and Zibriczky (2014) who showed the ability of entropy to measure risk in portfolio management.…”
Section: H X Tunindexsupporting
confidence: 92%
“…This finding is similar to that reported by Wagner and Low, with risk fades away with time. Then, we may conclude that entropy is sensitive to diversification corroborating thus the results of , Ormos and Zibriczky (2014).…”
Section: H X Tunindexsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, it is possible to state that in a closed system, the entropy never decreases, only increases. Nevertheless, according to Ormos and Zibriczky [46], entropy is a mathematically defined quantity, usually used to characterize the probability of results in a system that is undergoing a process.…”
Section: Entropymentioning
confidence: 99%
“…Ormos and Zibriczky [46] affirm that the functions of entropy can be divided into two main types: discrete and continuous entropy functions. Let X be a discrete random variable, the possible outcomes of that variable are x 1 , x 2 , ..., x n and the corresponding possibilities are…”
Section: Entropymentioning
confidence: 99%